HUBUNGAN POLA ASUH OTORITATIF DENGAN PRESTASI AKADEMIK PADA SISWA TUNARUNGU KATEGORI TULI KELAS VI SD DI BALI - Sanjiwani, Ida Ayu Maitry; Lestari, Made Diah (Jurnal Psikologi Udayana, 2014)
Currently mass media publish more about psychomotor achievement than academic achievement of students with hearing impairments, while in fact students with hearing impairments have the same intellectual capabilities as normal students. The difference lies in their intellectual development that tends to be sluggish due to limitations in hearing, communicating and using languages. Parenting styles adopted by parents have an important role in developing a child’s intellectual capability so as to achieve high academic achievement. When parents send their children in SLB B or State SLB show that parents applying authoritative parenting style in raising their children. This study aims to determine the relationship between authoritative parenting styles and the academic achievement of sixth grade elementary school students in Bali with hearing impairments in the deafness category. The subjects used in this study were sixth grade elementary school students with hearing impairments in the deafness category, who are attending SLB B (special school for hearing impaired children) or State SLB and living with their parents. The number of subjects used was as many as 28 students, which are the whole of the population. The authoritative parenting style scale reliability was 0.940. The result of the normality test on the authoritative parenting style was 0.426. The normality test result on academic achievement was 0.658. The linearity test result on the authoritative parenting style has probability (p) 0.000.  The analytical method used was the product moment correlation analysis. The correlation result in this study was 0.836 with probability (p) was 0,000. Based on the results it is seen that there is a positive relationship between authoritative parenting styles and academic achievement of sixth grade elementary school students in Bali with hearing impairments in the deafness category. This means that the stronger authoritative parenting style that are accepted, then there is increase academic achievement of sixth grade elementary school students in Bali with hearing impairments in the deafness category.   Keywords: authoritative parenting styles, academic achievement, students with hearing impairments